PENGARUH METODE MIMICRY-MEMORIZATION (MIM-MEM METHOD) DALAM MENINGKATKAN PENGUASAAN MUFRODAT PESERTA DIDIK DI MADRASAH ALIYAH AL BAIRUNY SAMBONGDUKUH JOMBANG - Karyani Karyani; Anggun Wulandari; Rina Dian Rahmawati (Al-Lahjah, 2019)
This study aims to determine "the effect of the Mimicry-Memorization Method (Mim-Mem Method) on the Mastery of Mufrodat in Madrasah Aliyah Al Bairuny Sambongdukuh Jombang". The purpose of using the Mimicry-Memorization (Mim-Mem Method) Method for mastering mufrodat in Madrasah Aliyah Al Bairuny is to facilitate students' understanding and mastery of mufrodat on Arabic learning material. Research with quantitative methods uses the type of experimental research (trials) with the type of ordinal data, while the data collection method uses the oral test method. The results of these data have proven that there is an effect of the Mimicry Memorization Method (Mim-Mem Method) on the mastery of mufrodat in Madrasah Aliyah Al Bairuny Sambongdukuh Jombang. The use of this method makes students more active and more effective in studying Arabic subjects, this is evidenced by the average results of oral tests with an average of class XI IPA 1 75.5 and XI IPA 2 with an average 69.8. Keywords: Mimicry Memorization Method, Mufrodat Mastery.